GAMBARAN BRAND EXPERIENCE DAN CUSTOMER-BASED BRAND EQUITY PADA SITUS WEDDING MARKETPLACE BRIDESTORY DI INDONESIA INDONESIA - Nurfitriani, Nurfitriani; Wibowo, Lili Adi; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - To find out the description of the level of brand experience and customer-based brand equity in site wedding marketplace Bridestory visitors in Indonesia. Design/methodology/approach - The design of this study is cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 135 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution.Findings - The result showed that brand experience is in good category, while customer-based brand equity is in good enough category. Â Originality / value - The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study